Stability of the D019 Chi (χ) and C14 laves phases in the γ-phase of chemically complex CoNi-base superalloys - Rajkowski, Maik; Schneider, Mike; Kostka, Aleksander; Somsen, Christoph; Fries, Suzana G.; Neumeier, Steffen; Laplanche, Guillaume (Journal of Alloys and Compounds, 2025)
The γ phases of CoNi-base superalloys are disordered solid solutions whose chemical complexity is similar to that of medium-entropy alloys. This study aims to investigate how compositional variations affect their thermal stability. As a starting point, the γ composition (Co55.5Ni23Al3.1Cr11.5W5Ti1Ta0.2Si0.7Hf0.03 in at.%) of a precipitation hardened γ/γ’ CoNi-base superalloy (ERBOCo-1), determined by atom probe tomography, was prepared as a bulk alloy. Nine alloys were then derived from this composition. First, four derivatives were designed by reducing the concentrations of one of the major elements (Co,Ni,Cr,W) by ∼5 at.% and compensating by increasing the concentrations of the other major elements, while keeping the contents of the minor elements (Al,Ti,Si,Ta,Hf) constant. In another set of five alloys, the compositions of the reference alloy and the first four derivatives were simplified to quaternary or ternary alloys of the Cr-Co-Ni-W system so that the ratios between the major elements remained the same. The alloys were cast, homogenized, cold-worked, and annealed for up to 1500 h followed by microstructural and chemical investigations. The results provide a better understanding of the effect of individual elements on the stability of geometrically (χ) and topologically close-packed phases (C14 laves and G) in CoNi-base medium-entropy alloys. The χ phase proved to be the most common secondary phase, which stability and compositional range are strongly underestimated in some current thermodynamic databases (e.g. TCNI10). Therefore, the present study provides new data that may help in their further development for CoNi-base superalloys and medium-entropy alloys.
CRIS-Team Scopus Importer:2025-04-01
Keywords: ERBOCo; Geometrically and topologically close-packed phases (GCP and TCP phases); Medium-entropy alloys (MEAs); TEM; ThermoCalc